Climate Classification, Hydrological, Agricultural, and Assessment of Climate Change Impacts Analysis in City of Pangkalpinang, Bangka Belitung Island Province, Indonesia - Ramadhani; Said, Ahmad (Cipasung Techno Pesantren: Jurnal Ilmiah, 2025)
This study assessed climate classification, hydrological conditions, and agricultural vulnerabilities in Pangkalpinang City, Bangka Belitung Province, Indonesia, using a 65-year (1959-2024) daily meteorological dataset. Climate classification revealed a dominant Af (Tropical Rainforest) type by the Köppen-Geiger method (occurring in 56 out of 66 years) with high precision (0.89-1.0) and a C1'As (perhumid mesothermal) classification predominating according to Thornthwaite (64 out of 66 years). Trend analysis showed a likely not significant temperature increase (approximately +0.02°C/year) and shifting precipitation patterns, with mean annual rainfall at 2289.84 mm and an annual precipitation concentration index (PCI) of 8.924, indicating a moderately irregular rainfall distribution. Hydrological analysis showed an average potential evapotranspiration (PET) of 0.284 mm, a soil moisture content of 99.751 mm, an average surface runoff of 4.577 mm, and 51 annual flood risk events, exhibiting a humid regime. Mean crop water requirement (CWR) was 4.857 relative units, and we observed a strong positive correlation (r=0.969) between the water requirement satisfaction index (WRSI) and crop water needs. The model validation exhibited a root mean square error (RMSE) between 0.1-0.5 and showed a stable Thornthwaite classification even with perturbations and the time series data analysis revealed the variability of parameters and a shift in temperature around the year 2000. These results emphasize the urgent need for localized climate adaptation strategies in Pangkalpinang.